Self-Control and Academic Achievement. [article]. - Duckworth, Angela L.
Self-control refers to the alignment of thoughts, feelings, and actions with enduringly valued goals in the face of momentarily more alluring alternatives. In this review, we examine the role of self-control in academic achievement. We begin by defining self-control and distinguishing it from related constructs. Next, we summarize evidence that nearly all students experience conflict between academic goals that they value in the long run and nonacademic goals that they find more gratifying in the moment. We then turn to longitudinal evidence relating self-control to academic attainment, course grades, and performance on standardized achievement tests. We use the process model of self-control to illustrate how impulses are generated and regulated, emphasizing opportunities for students to deliberately strengthen impulses that are congruent with, and dampen impulses that are incongruent with, academic goals. Finally, we conclude with future directions for both science and practice. -- (from the author)